2019
DOI: 10.2147/ccide.s204986
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of different combinations of surface treatment on adhesion of resin composite to zirconia</p>

Abstract: Purpose: The purpose of this laboratory study was to evaluate the effect of different surface treatment combinations on resin zirconia bonding. Materials and methods: One hundred and five pre-sintered zirconia quadrangles were prepared out of zirconia blocks, polished, then sintered and divided into five groups (n=21). Group I (control): samples were untreated, group II: grit-blasting with 50 µm alumina particles, group III: grit-blasting with 100 µm alumina particles, group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 62 publications
0
18
0
1
Order By: Relevance
“…APA is one of the most widely used protocol for modifying the surface topography of zirconia prior to cementation . It functions by removing loose contaminated surface, forming microretentive grooves, enlarging effective contact surface, and enhancing wettability on the intaglio surface of zirconia . Different types of particles ranging between 25‐ and 250‐μm can be used for hitting the surface at high speed .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…APA is one of the most widely used protocol for modifying the surface topography of zirconia prior to cementation . It functions by removing loose contaminated surface, forming microretentive grooves, enlarging effective contact surface, and enhancing wettability on the intaglio surface of zirconia . Different types of particles ranging between 25‐ and 250‐μm can be used for hitting the surface at high speed .…”
Section: Discussionmentioning
confidence: 99%
“…Ghasemi et al suggested 3 W Er,Cr:YSGG LI as an alternative surface treatment for zirconia after sintering process . Another study by Saade et al proved that Er,Cr:YSGG LI with a 5.5 W power‐output enhanced the bonding ability to zirconia . As high laser‐power settings may lead to overheating and undermine zirconia's structural properties, irradiation time and power‐output of lasers should be well‐considered .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…기계적인 결합을 위한 표면처리 방법으로는 airborne-particle abrasion (APA) [12][13][14], erbium:yttrium-aluminum-garnet (Er:YAG) 레이저 표면처리 [15,16], 불산을 이용한 표면 에칭처리 [17][18][19]…”
unclassified
“…, Inokoshi et al (5), Cheung & Botelho (28), Saade et al(29) andLiu et al (30), where Cheung& Botelho(28) andLiu et al (30) found de-bonded specimens of the as-sintered group that could not even withstand the aging treatments and got de-bonded before application of SBS test.The highest SBS values obtained by the sandblasted subgroup in our study, could be related to the uniform existence of superficial irregularities and shallow scratches all over the examined surface, that was related to the effect of hitting the surface by the sharp abrasive particles creating retentive spaces accompanied with the presence of some impinged abrasive particles on the ultra-translucent zirconia surface by the force of blasting pressure that led toincreased available surface area for obtaining a micro-mechanical bond with the adhesive resin resulting in the highest shear bond strength results, this was in agreement with, Aung et al (31), Hallmann et al (14), Kern M (11), LE et al (17), Liu et al (30), Thammajaruk et al (13), Tzanakakis et al (10) and Zhao et al (32), who stated that air-abrasion at a moderate pressure xii provided a reliable bonding to zirconia based restorations, particularly when combined with phosphate monomer containing primers and/or luting resins as it appeared in this study. However, this was in disagreement with other studies done by Lee et al (2019) (24), Lee & Lee (33), Xie et al…”
mentioning
confidence: 99%